Foam rubber for folding screen and preparation method of foam rubber

By adopting a multi-layer structure designed foam glue for folding screens, combined with nanoparticle reinforcements and self-healing functional materials, the problems of fatigue and poor durability of single-layer foam glue are solved, achieving both high elasticity and high strength. , significantly extending the service life of the equipment.

CN119331523APending Publication Date: 2025-01-21SUZHOU YUNSHANG ELECTRONIC CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411454788.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Due to the single-layer structure, the existing folding screen foam glue is prone to fatigue and has poor durability, and cannot take into account both high elasticity and high strength, resulting in a decrease in elastic recovery ability during frequent folding and deployment, affecting the durability of the equipment.

Method used

Bubble glue with a multi -layer structure design, including foam base material layer, primer coating layer, enhanced layer and black glue layer. Elastic recovery ability, coating nanosane coating on the surface to improve abrasion resistance and anti -aging performance.

Benefits of technology

It significantly improves the fatigue resistance and mechanical strength of the foam rubber, extends the service life of the equipment, reduces the frequency of replacement, and improves the wear resistance and anti-aging performance of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331523A_ABST
    Figure CN119331523A_ABST
Patent Text Reader

Abstract

The present invention relates to the field of display equipment, and discloses a foam adhesive for a folding screen and a preparation method thereof, the foam adhesive comprises: a foam base material layer prepared from polyurethane foam or an ethylene-vinyl acetate copolymer; the bottom gluing layer is attached to at least one surface of the foam base material layer, the thickness of the bottom gluing layer is 10-30 microns, and the bottom gluing layer is composed of solvent type acrylic acid glue with the solid content of 50% and black color paste; the reinforcing layer is positioned between the bottom coating glue layer and the foam base material, the reinforcing layer contains a nano-particle reinforcing agent, and the nano-particle reinforcing agent comprises 0.5 to 2 weight percent of nano silicon dioxide and 0.1 to 1 weight percent of graphene oxide; and the black adhesive layer is arranged on the outer side of the bottom adhesive coating layer. By adopting the multi-layer structural design, the mechanical strength of the foam rubber can be enhanced while high elasticity is provided, and the anti-fatigue performance of the foam rubber is remarkably improved. It is ensured that the foam rubber can still keep excellent elastic recovery capacity in long-time high-frequency folding use, and the service life of folding screen equipment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of display devices, and in particular to a foam adhesive for a folding screen and a preparation method thereof. Background Art

[0002] With the continuous development of folding screen technology, flexible electronic devices, such as folding screen mobile phones and tablets, have become a hot spot in the market. In order to achieve the stability and durability of folding screens, foam glue is widely used as a key material. However, the existing folding screen foam glue still has many technical deficiencies in actual use.

[0003] Traditional foam adhesives are usually single-layer structures, which cannot provide both high elasticity and high strength. During frequent folding and unfolding, single-layer foam adhesives are prone to fatigue, resulting in a gradual decrease in their elastic recovery ability, which ultimately affects the durability of the device. This structure often deforms or even fails when used for a long time. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a foam adhesive for a folding screen and a preparation method thereof, which solves the problem that the foam adhesive with a single-layer structure is prone to fatigue and has poor durability.

[0005] To achieve the above purpose, the present invention is implemented through the following technical solutions: A foam adhesive for a folding screen, comprising:

[0006] A foam substrate layer, wherein the foam substrate layer is made of polyurethane foam or ethylene-vinyl acetate copolymer, has a thickness of 0.5 to 1.5 mm, and an elastic recovery rate of not less than 85%;

[0007] A primer layer, the primer layer is attached to at least one side of the foam substrate layer, has a thickness of 10 to 30 μm, and is composed of a solvent-based acrylic glue with a solid content of 50% and a black color paste, wherein the content of the black color paste is 10 to 20 parts, and the viscosity of the acrylic glue is 3000 to 6000 cps;

[0008] A reinforcing layer is located between the primer layer and the foam substrate, the reinforcing layer contains a nanoparticle reinforcing agent, the nanoparticle reinforcing agent includes 0.5-2wt.% nano-silicon dioxide and 0.1-1wt.% graphene oxide, the thickness of the reinforcing layer is 5-20 μm, and is used to improve the compression strength and elastic recovery ability of the foam adhesive;

[0009] The black adhesive layer is arranged on the outer side of the base adhesive layer, has a thickness of 10 to 30 μm, a peeling force of the dry adhesive of ≥18N / 25mm, and a light transmittance of ≤1%.

[0010] Preferably, the particle size of the nano-silicon dioxide in the reinforcement layer is 10 to 30 nm, and the flake size of the graphene oxide is 100 to 500 nm.

[0011] Preferably, the foam adhesive contains a self-repairing functional material, which includes 1 to 5 wt.% of a thermal responsive polymer or a photoresponsive polymer, and can repair microcracks by local heating or UV irradiation.

[0012] Preferably, the thermally responsive polymer is polyethylene oxide or polyvinyl alcohol, which can achieve molecular chain movement and microcrack repair through thermal activation in the range of 60-100°C.

[0013] Preferably, the photoresponsive polymer contains a photosensitive group, which triggers a cross-linking reaction under UV light of 365 to 395 nm.

[0014] Preferably, the surface of the foam substrate layer is coated with a 5-20 μm thick nano-silane coating, which is evenly coated by spin coating or spray coating.

[0015] Preferably, the nano-silane coating contains 0.5-2 wt.% of nano-titanium dioxide or zinc oxide particles, and the nano-silane coating is applied by spin coating or spray coating.

[0016] Preferably, a method for preparing foam glue for folding screen comprises the following steps:

[0017] S1: Prepare a foam substrate with a thickness of 0.5-1.5 mm, and evenly coat the surface with a 10-30 μm thick primer layer, wherein the primer layer contains 50% solid content of acrylic glue and 10-20 parts of black color paste;

[0018] S2: coating a reinforcement layer on at least one side of the primer substrate, wherein the thickness of the reinforcement layer is 5 to 20 μm, and the reinforcement layer comprises nano-silicon dioxide and graphene oxide;

[0019] S3: coating a black adhesive layer with a thickness of 10 to 30 μm on the reinforcing layer and curing it at 120 to 150° C.;

[0020] S4: Using nano-coating technology, a 5-20 μm thick nano-silane coating is applied on the surface of the foam substrate by spin coating or spray coating process.

[0021] The present invention provides a foam adhesive for a folding screen and a preparation method thereof. It has the following beneficial effects:

[0022] 1. The multi-layer structure design adopted by the present invention can provide high elasticity while enhancing the mechanical strength of the foam glue, significantly improving its anti-fatigue performance. This design ensures that the foam glue can still maintain excellent elastic recovery ability during long-term high-frequency folding use, extending the service life of the folding screen device.

[0023] 2. The present invention can significantly improve the compression strength and elastic recovery performance of the foam adhesive after folding by introducing a reinforcing layer containing nanoparticles (such as nano-silicon dioxide and graphene oxide) into the foam adhesive. This allows the foam adhesive to quickly recover to its original shape after multiple foldings and is not prone to permanent deformation.

[0024] 3. The present invention introduces materials with self-repairing function (such as heat-responsive and light-responsive polymers) so that when the foam adhesive is slightly damaged or has microcracks, it can trigger a repair reaction through heating or UV light. This function reduces the replacement frequency of the foam adhesive, significantly extends the service life of the equipment and reduces maintenance costs.

[0025] 4. The present invention applies a nano-silane coating on the surface of the foam substrate, which significantly improves the wear resistance, aging resistance and hydrophobicity of the foam adhesive, ensuring that it still maintains a good appearance and performance during long-term use. This surface improvement effectively solves the problems of uneven color and uneven thickness of the foam adhesive surface in the prior art, and improves the aesthetics of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The present invention is a flow chart of a method for preparing foam adhesive for folding screens. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Please refer to the attached Figure 1 The embodiment of the present invention provides a foam adhesive for a folding screen, comprising:

[0029] 1. Foam substrate layer

[0030] Material selection

[0031] The foam substrate layer uses polyurethane foam (PU) or ethylene-vinyl acetate copolymer (EVA), which have excellent elasticity and durability, and can provide reliable cushioning performance during the repeated folding and unfolding of the folding screen.

[0032] Thickness control: The thickness of the foam substrate layer is 0.5-1.5 mm. This thickness range can ensure sufficient elasticity while maintaining the slim design of the folding screen, meeting the thickness requirements of modern display devices.

[0033] Elastic recovery rate: The elastic recovery rate of the foam substrate is not less than 85%, which ensures that it can quickly restore its original shape after folding and reduce permanent deformation after long-term use.

[0034] 2. Primer layer

[0035] Function and materials

[0036] The base coating is used to enhance the adhesion between the foam substrate and the folding screen device, and its thickness is 10 to 30 μm. The glue used is a solvent-based acrylic glue with a solid content of 50%, and black color paste is added.

[0037] Characteristics of acrylic glue: Viscosity is 3000-6000cps, which ensures good fluidity and curing performance during the coating process.

[0038] The content of black color paste is 10 to 20 parts (by mass ratio). Through the control of black color paste, the primer layer not only has high-strength adhesion performance, but also can effectively shield the color difference of the bottom layer and improve the appearance consistency.

[0039] 3. Enhancement layer

[0040] Enhanced Materials and Effects

[0041] The thickness of the reinforcement layer is controlled at 5 to 20 μm, and the overall strength and elastic recovery performance of the foam adhesive are mainly improved by adding nanoparticle reinforcements (including nano silicon dioxide (SiO2) and graphene oxide (GO)).

[0042] Content and particle size of nano-silicon dioxide: The content of nano-silicon dioxide is 0.5-2wt.%, and the particle size is 10-30nm, which can effectively improve the compression strength and wear resistance of the foam glue.

[0043] Graphene oxide content and flake diameter: The graphene oxide content is 0.1-1wt.%, and its flake diameter is 100-500nm. Through its excellent mechanical properties, the elasticity and durability of the foam adhesive are further improved.

[0044] The addition of the reinforcement layer can ensure that the foam glue can effectively buffer the pressure during folding and unfolding, reduce material fatigue, and maintain good elastic recovery ability after being folded tens of thousands of times.

[0045] 4. Black glue layer

[0046] Design and performance of black glue layer

[0047] The black adhesive layer is arranged on the outside of the base adhesive layer, with a thickness of 10 to 30 μm, and has the following functions:

[0048] Peeling force: The peeling force of the dry glue is ≥18N / 25mm, ensuring that the foam glue has sufficient bonding strength when adhering to the folding screen device.

[0049] Light transmittance: The light transmittance of the black glue layer is ≤1%, which effectively blocks the passage of light, avoids reflection or light leakage in the device, and ensures the visual effect of the screen.

[0050] 5. Self-healing functional materials

[0051] In order to extend the service life of the foam adhesive, the present invention introduces 1-5wt.% of self-repairing functional materials, which include thermal responsive polymers or photoresponsive polymers, and can self-repair through thermal or light stimulation when microcracks are generated.

[0052] Thermally responsive polymers: such as polyethylene oxide (PEO) or polyvinyl alcohol (PVA), when heated to 60-100°C, the polymer chains move, filling the cracks and restoring the integrity of the material. The repair rate can reach over 90%.

[0053] Photoresponsive polymers: Polymers containing photosensitive groups can trigger cross-linking reactions under UV light of 365-395nm, achieving self-healing of cracks, and are suitable for repair operations under controllable light environments.

[0054] 6. Nano coating

[0055] Function and coating process of nano coating

[0056] In order to improve the surface performance of the foam substrate, the present invention coats a 5-20 μm thick nano-silane coating on the surface of the foam substrate to enhance its wear resistance, hydrophobicity and anti-aging performance.

[0057] Coating composition: The nano-silane coating contains 0.5-2wt.% of nano-titanium dioxide (TiO2) or zinc oxide (ZnO) particles, which can effectively improve the anti-ultraviolet performance of the foam glue and delay the aging process.

[0058] Coating process: Spin coating or spray coating technology is used to ensure the uniformity and surface smoothness of the coating. This process ensures high adhesion and surface quality of the coating, further improving the durability and surface stability of the foam adhesive.

[0059] A method for preparing foam glue for folding screens comprises the following steps:

[0060] S1: Preparation of foam substrate

[0061] Select substrate material: Choose polyurethane foam (PU) or ethylene-vinyl acetate copolymer (EVA) with a thickness of 0.5-1.5 mm as the foam substrate. These materials have good elasticity, compressibility and recovery, and can meet the needs of folding screen devices for repeated folding and unfolding.

[0062] Surface treatment: Pre-treat the surface of the foam substrate to ensure good adhesion of the subsequent adhesive layer. Plasma treatment or heat treatment can be used to remove surface contaminants and increase surface activity to ensure a strong bond between the coating and the foam substrate.

[0063] Coating of the primer layer: Mix 50% solid content solvent-based acrylic glue and black color paste in proportion, the specific ratio is 10-20 parts of black color paste and 100 parts of acrylic glue, and the viscosity is controlled at 3000-6000cps. Use scraping or spraying technology to evenly coat the mixed primer layer on at least one side of the foam substrate, with a coating thickness of 10-30μm. During the coating process, the uniformity of the glue layer should be ensured to avoid bubbles or local uneven thickness.

[0064] Curing treatment: After the primer layer is applied, it is pre-cured at 80-120°C for about 10-15 minutes to allow the glue layer to be initially shaped and its surface hardness to be increased.

[0065] S2: Coating of reinforcement layer

[0066] Preparation of reinforcing materials: Prepare a reinforcing coating solution containing a nanoparticle reinforcing agent, the reinforcing agent includes 0.5-2wt.% nano silicon dioxide (SiO2) and 0.1-1wt.% graphene oxide (GO), and the particle sizes of the two are 10-30nm and 100-500nm respectively. The reinforcing agent is mixed with acrylic glue in proportion to ensure that the reinforcing agent is evenly dispersed in the glue.

[0067] Coating of the reinforcement layer: Spin coating or scraping process is used to evenly coat the reinforcement layer solution on the base coating substrate, and the coating thickness is controlled at 5 to 20 μm. During coating, special attention should be paid to controlling the uniformity of the coating to prevent particle accumulation or local uneven coating.

[0068] Curing treatment: After coating, the reinforcement layer is cured at 120-150°C for 10-20 minutes. After curing, the reinforcement layer can provide sufficient mechanical strength and elastic recovery performance to cope with the stress of repeated folding of the folding screen device.

[0069] S3: Coating of black adhesive layer

[0070] Preparation of black glue layer: prepare black glue layer solution, the main components are solvent-based acrylic glue and black color paste, with a mass ratio of 50% solid content. After mixing the black color paste and acrylic glue evenly, ensure that the content of black color paste is 10-20 parts and the viscosity of the glue is 3000-6000cps.

[0071] Coating process: Spray or scrape the black glue solution evenly on the surface of the reinforcement layer, and control the coating thickness to 10-30μm. During the coating process, the uniformity of the glue layer must be ensured to avoid light transmission or uneven color difference in the glue layer, and to ensure the visual effect of the black glue layer.

[0072] Curing treatment: After the black adhesive layer is coated, it needs to be finally cured in an environment of 120-150°C for 20-30 minutes. After curing treatment, the black adhesive layer can have a peel strength of ≥18N / 25mm and a light transmittance of ≤1%.

[0073] S4: Application of Nano-Silane Coating

[0074] Preparation of nano coating solution: Prepare a nano silane coating solution, the coating contains 0.5-2wt.% nano titanium dioxide (TiO2) or zinc oxide (ZnO) particles, the particle size is 20-50nm, which can enhance the surface wear resistance and UV resistance of the foam substrate.

[0075] Coating process: Spin coating or spray coating is used to evenly coat the nano-silane coating on the surface of the foam substrate, and the coating thickness is controlled at 5 to 20 μm. The spin coating process speed should be controlled between 1000 and 3000 rpm to ensure the uniformity and surface smoothness of the coating and prevent uneven thickness.

[0076] Curing treatment: After coating, the coating is cured at 100-120°C for 10-20 minutes. The cured nano-silane coating can improve the hydrophobicity and surface hardness of the foam substrate, with a contact angle of ≥110°, significantly improving the durability and anti-aging ability of the foam substrate.

[0077] The foam adhesive prepared by the above steps has excellent mechanical strength, elastic recovery ability, wear resistance and self-repairing function, and can meet the needs of frequent folding of folding screen devices. Parameters such as temperature, time and coating thickness in each step need to be strictly controlled to ensure that the overall performance of the foam adhesive meets the expected standards.

[0078] The following is an introduction in conjunction with specific embodiments:

[0079] Embodiment 1:

[0080] Foam substrate thickness: 0.5mm

[0081] Elastic recovery rate: 85%

[0082] Primer layer thickness: 10μm

[0083] Black color paste content: 10 parts

[0084] Acrylic glue viscosity: 3000cps

[0085] Reinforcement layer thickness: 5μm

[0086] Nano-silicon dioxide content: 0.5wt.%

[0087] Nano-silicon dioxide particle size: 10nm

[0088] Graphene oxide content: 0.1wt.%

[0089] Graphene oxide sheet diameter: 100nm

[0090] Black glue layer thickness: 10μm

[0091] Peel force: 18N / 25mm

[0092] Light transmittance: 1%

[0093] Nanosilane coating thickness: 5μm

[0094] Nano titanium dioxide content: 0.5wt.%

[0095] Contact angle: 110°

[0096] Embodiment 2:

[0097] Foam substrate thickness: 1.0mm

[0098] Elastic recovery rate: 90%

[0099] Primer layer thickness: 20μm

[0100] Black color paste content: 15 parts

[0101] Acrylic glue viscosity: 4500cps

[0102] Reinforcement layer thickness: 12μm

[0103] Nano-silicon dioxide content: 1.0wt.%

[0104] Nano-silicon dioxide particle size: 20nm

[0105] Graphene oxide content: 0.5wt.%

[0106] Graphene oxide sheet diameter: 300nm

[0107] Black glue layer thickness: 20μm

[0108] Peel force: 20N / 25mm

[0109] Light transmittance: 0.5%

[0110] Nanosilane coating thickness: 10μm

[0111] Nano titanium dioxide content: 1.0wt.%

[0112] Contact angle: 115°

[0113] Embodiment 3:

[0114] Foam substrate thickness: 1.5mm

[0115] Elastic recovery rate: 95%

[0116] Primer layer thickness: 30μm

[0117] Black color paste content: 20 parts

[0118] Acrylic glue viscosity: 6000cps

[0119] Reinforcement layer thickness: 20μm

[0120] Nano-silicon dioxide content: 2.0wt.%

[0121] Nano-silicon dioxide particle size: 30nm

[0122] Graphene oxide content: 1.0wt.%

[0123] Graphene oxide sheet diameter: 500nm

[0124] Black glue layer thickness: 30μm

[0125] Peel force: 25N / 25mm

[0126] Light transmittance: 0.1%

[0127] Nanosilane coating thickness: 20μm

[0128] Nano titanium dioxide content: 2.0wt.%

[0129] Contact Angle: 120°.

[0130] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A foam adhesive for a folding screen, characterized in that: include: A foam substrate layer, wherein the foam substrate layer is made of polyurethane foam or ethylene-vinyl acetate copolymer, has a thickness of 0.5 to 1.5 mm, and an elastic recovery rate of not less than 85%; A primer layer, the primer layer is attached to at least one side of the foam substrate layer, has a thickness of 10 to 30 μm, and is composed of a solvent-based acrylic glue with a solid content of 50% and a black color paste, wherein the content of the black color paste is 10 to 20 parts, and the viscosity of the acrylic glue is 3000 to 6000 cps; A reinforcing layer is located between the primer layer and the foam substrate, the reinforcing layer contains a nanoparticle reinforcing agent, the nanoparticle reinforcing agent includes 0.5-2wt.% nano-silicon dioxide and 0.1-1wt.% graphene oxide, the thickness of the reinforcing layer is 5-20 μm, and is used to improve the compression strength and elastic recovery ability of the foam adhesive; The black adhesive layer is arranged on the outer side of the base adhesive layer, has a thickness of 10 to 30 μm, a peeling force of the dry adhesive of ≥18N / 25mm, and a light transmittance of ≤1%.

2. The foam adhesive for folding screen according to claim 1, characterized in that: The particle size of the nano silicon dioxide in the reinforcement layer is 10-30 nm, and the sheet size of the graphene oxide is 100-500 nm.

3. The foam adhesive for folding screen according to claim 1, characterized in that: The foam adhesive contains a self-repairing functional material, which includes 1 to 5 wt.% of a thermal response polymer or a light response polymer and can repair microcracks by local heating or UV irradiation.

4. The foam adhesive for folding screen according to claim 3, characterized in that: The thermal responsive polymer is polyethylene oxide or polyvinyl alcohol, which can achieve molecular chain movement and microcrack repair through thermal activation within the range of 60-100°C.

5. The foam adhesive for folding screen according to claim 3, characterized in that: The photoresponsive polymer contains a photosensitive group, which triggers a cross-linking reaction under UV light of 365 to 395 nm.

6. The foam adhesive for folding screen according to claim 1, characterized in that: The surface of the foam substrate layer is coated with a 5-20 μm thick nano-silane coating, which is evenly coated by a spin coating or spray coating process.

7. The foam adhesive for folding screen according to claim 1, characterized in that: The nano-silane coating contains 0.5-2 wt.% of nano-titanium dioxide or zinc oxide particles, and the nano-silane coating is coated by spin coating or spray coating.

8. A method for preparing a foam adhesive for a folding screen, used for the foam adhesive for a folding screen as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: S1: Prepare a foam substrate with a thickness of 0.5-1.5 mm, and evenly coat the surface with a 10-30 μm thick primer layer, wherein the primer layer contains 50% solid content of acrylic glue and 10-20 parts of black color paste; S2: coating a reinforcement layer on at least one side of the primer substrate, wherein the thickness of the reinforcement layer is 5 to 20 μm, and the reinforcement layer comprises nano-silicon dioxide and graphene oxide; S3: coating a black adhesive layer with a thickness of 10 to 30 μm on the reinforcing layer and curing it at 120 to 150° C.; S4: Using nano-coating technology, a 5-20 μm thick nano-silane coating is applied on the surface of the foam substrate by spin coating or spray coating process.